VERIFICATION OF DRYING SOIL-WATER CHARACTERISTIC CURVE OF CRUSHED COMPACTER CLAY SHALE MEASURED WITH FILTER PAPER METHOD - SALSABILA RAMADHANI, HASNAA
In Indonesia, clay shale land is a soil that is problematic in practical engineering. There hasn't been much research on clay shale so it's difficult to analyze when this soil is found in the field. Clay shale is strongly influenced by saturated-unsaturated conditions so the saturated-unsaturated soil mechanics need to be quantified. Quantification of saturated-unsaturated mechanics relies heavily on soil-water characteristic curves (SWCC). Previously, SWCC has been studied in compacted clay shale using the filter paper method. In this method, the equilibrium time used is 15 days. The main research on this thesis is to verify whether the equilibrium time used is appropriate or not. In ASTM D5298-16, it is written that the recommended equilibrium time is a minimum of seven days. However, these recommendations have not been based on appropriate research. Laboratory testing by varying the time of equilibrium resulted in an equilibrium time value on moisture content 10% and 20% is 3 and 21 days respectively. The equilibrium time on moisture content at 30% has not produced a good value so it is still cannot be concluded. SWCC correction is done using matric suction that has reached equilibrium, which is at water content of 10% and 20%. Numerical modeling is done based on laboratory testing. By doing back-analysis at water content of 10% and 20%, the prediction of equilibrium time at 30% water content is 34 days. From the corrected SWCC, the volume change constitutive surface and extended Mohr-Coulomb failure envelope can be determined. Both of these are applications of SWCC into practical engineering. The constitutive surface of volume change is performed using a corrected SWCC curve and a consolidation curve. The failure envelope can be determined using saturated triaxial testing result and air-entry values on SWCC.